Camping out in the Yellowstone, 1882 - Richards, Mary Bradshaw, 1825- (University of Utah Press, 1994)
"Camping Out in the Yellowstone, 1882 describes the park at a time when Yellowstone was truly an "out-back and beyond" experience." "Writing just five years after the army chased the Nez Perce Indians through the area, and only ten years after the parks's establishment, Mary Richards provides a vivid picture of the undeveloped and untouristed Yellowstone Park: Fire Hole Basin, Mammoth Hot Springs, Lower Falls, and the Excelsior Geyser, now defunct but mightier at the time than Old Faithful." "Augmented by twenty-eight contemporary photographs, Camping Out in the Yellowstone offers a fascinating perspective for present-day park lovers."--Jacket.